2005
DOI: 10.4049/jimmunol.175.1.591
|View full text |Cite
|
Sign up to set email alerts
|

Response of Memory CD8+ T Cells to Severe Acute Respiratory Syndrome (SARS) Coronavirus in Recovered SARS Patients and Healthy Individuals

Abstract: To date, the pathogenesis of severe acute respiratory syndrome (SARS) in humans is still not well understood. SARS coronavirus (SARS-CoV)-specific CTL responses, in particular their magnitude and duration of postinfection immunity, have not been extensively studied. In this study, we found that heat-inactivated SARS-CoV elicited recall CTL responses to newly identified spike protein-derived epitopes (SSp-1, S978, and S1202) in peripheral blood of all HLA-A*0201+ recovered SARS patients over 1 year postinfectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
93
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(95 citation statements)
references
References 51 publications
2
93
0
Order By: Relevance
“…Furthermore, the function of non-lymphoid effector memory cells has been demonstrated in a study in which Sendai virus specific memory CD4 + T cells persist in the lungs, and transfer of these cells into ␤2-microglobulin-dificient mice confers a significant level of protection against re-infection [24]. Consistent with our observations, several reports demonstrate that natural infection in humans induces memory CD8 + T cells responses [10]. Moreover, immunization of mice with adno-vector encoding codon-optimized SARS-CoV S protein generates two H-2 brestricted epitopes and one H-2 d -restricted epitopes of CD8 + T cells [25].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Furthermore, the function of non-lymphoid effector memory cells has been demonstrated in a study in which Sendai virus specific memory CD4 + T cells persist in the lungs, and transfer of these cells into ␤2-microglobulin-dificient mice confers a significant level of protection against re-infection [24]. Consistent with our observations, several reports demonstrate that natural infection in humans induces memory CD8 + T cells responses [10]. Moreover, immunization of mice with adno-vector encoding codon-optimized SARS-CoV S protein generates two H-2 brestricted epitopes and one H-2 d -restricted epitopes of CD8 + T cells [25].…”
Section: Discussionsupporting
confidence: 90%
“…These antibodies could inhibit the infection of cells with pseudotyped lentiviral particles bearing SARS-CoV S protein and be used to treat SARS-CoV-infected patients [4][5][6][7]. Recently, several reports including ours have demonstrated that SARS-CoV S specific memory CD8 + T cells were generated and maintained in vivo in the patients with fully recovered from SARS-CoV infection [8][9][10]. These data indicate that the spike protein is a good target for the vaccine to generate immune responses against the SARS-CoV infection.…”
Section: Introductionmentioning
confidence: 99%
“…Studies of the immune response to coronaviruses suggest that both humoral and cellular immunity contribute to protection (61)(62)(63)(64). Recently, existence of memory CTLs against SSp-1, S978, and S1203 epitopes was reported in SARS-recovered patients over 1 year postinfection, and dual roles of CTLs in control of virus replication and immunopathology of acute SARS-CoV infection were suggested (65). It has been proved that DNA vaccine encoding the SARS-CoV S protein may induce effective T cell and neutralizing Ab responses as well as protective immunity in a mouse model (23).…”
Section: Discussionmentioning
confidence: 99%
“…Two HLA-A2-restricted T cell epitopes in the S protein of SARS-CoV were immunogenic and elicited an overt specific T cell response in patients who survived SARS (130). Stimulation with inactivated SARS-CoV induced a memory CTL response in recovered SARS patients (131) and selective expansion of effector/memory Vγ9Vδ2 T cells. This expansion was associated with higher anti-SARS IgG levels.…”
Section: Innate Immune Response To Sars-covmentioning
confidence: 98%